Specification of a cyber-political entrepreneurship model. - García Lirios, Cruz (2014)
The formation civic politics supposes the participation sociopolitical of digital entrepreneurs as agents of change. In the age of the information, the company is shaped by civil spheres that not only look for a major deregulation of the State in the matters sociopolitical; but, to look for a major participation as the bureaucracy transforms.